The relationship between the nail and systemic enthesitis in psoriatic arthritis. Issue 3 (19th November 2021) - Elliott, Ashley; Pendleton, Adrian; Wright, Gary; Rooney, Madeleine
Abstract: Objective: Psoriatic nail disease is more common in PsA than in isolated skin psoriasis (PsO). The nail is closely integrated to the DIP joint entheses. US data have shown that those patients with nail disease in PsO are more likely to have systemic enthesitis. We examined whether there was a relationship between nail disease, DIP enthesitis and systemic enthesitis in established PsA. Methods: Forty-six PsA participants with nail disease underwent US scanning of the nail unit and the DIP entheses along with peripheral entheseal sites according to the Madrid sonographic enthesitis index (MASEI). Results: At the finger level, there was a mild to moderate correlation between nail US changes and both clinical nail disease and DIP enthesis changes (DIP US) [Spearman correlation ( r S ) = 0.30, P < 0.001 and r S = 0.16, P < 0.001, respectively]. At the patient level, there was a moderate correlation between the nail US score and nail psoriasis severity index score and DIP US ( r S = 0.33, P = 0.024 and r S = 0.43, P = 0.003, respectively). At the patient level, there was also a positive correlation between a higher nail US score and the active peripheral enthesitis score (MASEI-active) ( r S = 0.35, P = 0.018). When power Doppler was part of nail US score, similar results were demonstrated at both the finger and patient levels. Conclusion: This study has demonstrated the utility of nail US imaging and the close relationship, on scanning, between the DIP entheses and the nail unit. In PsA, we have seen a correlation between active US changes at the nail and peripheral enthesitis, which requires further analysis. Trial registration: ClinicalTrials.gov, https://clinicaltrials.gov, NCT03955861.